OPERATIONS ON THE CAROTID ARTERIES FOR ACUTE PERIOD OF ISCHEMIC STROKE - Mikhail S. Mikhailov; Aleksander V. Vavilov; Andrey I. Gritsaenko; Vladimir Yu. Ridel; Aleksey V. Novozhilov; Anar B. Musaev; Evgeniy G. Eidlin; Natal’ya Yu. Zelenkina (Креативная хирургия и онкология)
Introduction. The study reviewed the experience of surgical treatment of 145 patients in Samara State Clinical Hospital (SSCH) №1 named after N.I. Pirogov, city of Samara, during the period 2013 - 2016, which had 146 reconstructive operations on carotid arteries during acute period of ischemic stroke. Materials and methods. Indications for urgent intervention were 3 groups of clinicalmorphological criteria (analysis groups): 1. Stenosis of the internal carotid artery  (ICA) over 55% of lumen with unstable neurological symptoms; stenosis of ICA more than 70% of lumen with stable neurological symptoms; heterogeneous atherosclerotic plaque with tire defect, according to  colour duplex ultrasonography of brachiocephalic artery – in 94 patients, 81 of them have undergone everting  carotid endarterectomy (CEAE), 13 of them -CEAE with plasty of the autovenous patch.  2. Pathological tortuosity of ICA on the side of symptom-based brain injury in combination with or without stenosis + unstable neurologic symptoms - in 22 patients, 18 of them have undergone everting CEAE in combination with resection of ICA, 4 patients have undergone resection of ICA and elimination of pathologic tortuosity. 3. Thrombotic occlusion of ICA on the side of the stroke, regardless of stability of neurological symptoms - in 29 patients, 17 of them have undergone resection of ICA with plasty of the external carotid artery, 6 patients have undergone thrombendarterectomy from ICA with plasty with the autovenous patch, 6 patients have undergone everting CEAE for thrombotic occlusion of ICA. Results. By the time of discharge from the hospital the regression of neurological symptoms reported for 124 (85%) patients. Early lethality was 3.4%. Conclusions. Thus, the findings allow considering that under conditions of multispeciality hospital, with strict compliance with the selection criteria, the surgical treatment on the brachiocephalic vessel in the acute period of ischemic stroke, has the right to be regarded as one of the most effective treatments for this disease.